(untitled) (Research, Society and Development, 2022)
Stillman’s cleft (Sc) is a mucogingival defect of traumatic etiology, which if left untreated could progress to a true gingival recession with esthetic consequences, hypersensitivity, carious and non-carious lesions. The aim of this article was to describe a case report of Stillman’s cleft that evolved into true gingival recessions treated surgically. A search was made for relevant articles on the subject, surgical technique used and results obtained, using inclusion and exclusion criteria. A 42-year-old woman comes for private consultation with Dr. C.C to treat V-shaped lesions that due to their clinical characteristics were compatible with Stillman’s cleft, which evolved into true Cairo class II gingival recessions. The surgical procedure was performed using a modified coronally advanced tunnel technique with subepithelial connective tissue graft and approximation of the lateral edges of the recessions. The healing of both the surgical site and the graft sites progressed without complications within normal soft tissue healing patterns. A 6-month follow-up was carried out during which 100% coverage of the root surfaces was observed, an increase of adherent gingiva was evidenced in the treated areas. The modified coronally advanced tunnel technique with subepithelial connective tissue grafting and approximation of the lateral edges of recessions provides good esthetic and functional results for treating Stillman’s clefts that evolved into true gingival recessions.